L‐Fucose prevention of renal ischaemia/reperfusion injury in Mice. Issue 1 (27th November 2019) - Howard, Mark C.; Nauser, Christopher L.; Farrar, Conrad A.; Wallis, Russell; Sacks, Steven H.
Abstract: In a recent study, we identified a fucosylated damage‐associated ligand exposed by ischemia on renal tubule epithelial cells, which after recognition by collectin‐11 (CL‐11 or collectin kidney 1 (CL‐K1)), initiates complement activation and acute kidney injury. We exploited the ability to increase the local tissue concentration of free l ‐fucose following systemic administration, in order to block ligand binding by local CL‐11 and prevent complement activation. We achieved a thirty‐five‐fold increase in the intrarenal concentration of l ‐fucose following an IP bolus given before the ischemia induction procedure ‐ a concentration found to significantly block in vitro binding of CL‐11 on hypoxia‐stressed renal tubule cells. At this l ‐fucose dose, complement activation and acute post‐ischemic kidney injury are prevented, with additional protection achieved by a second bolus after the induction procedure. CL‐11 −/− mice gained no additional protection from l ‐fucose administration, indicating that the mechanism of l ‐fucose therapy was largely CL‐11‐dependent. The hypothesis is that a high dose of l ‐fucose delivered to the kidney obstructs the carbohydrate recognition site on CL‐11 thereby reducing complement‐mediated damage following ischemic insult. Further work will examine the utility in preventing post‐ischemic injury during renal transplantation, where acute kidney injury is known to correlate with poor graft survival.